Studies of the comparative efficacy of alcoholic extracts of Bironja, Turmeric, and Veranda leaves with that of patent drug Nilzan agains trematodiasis in sheep - Begum, Tahmina; Rahman, Bayzer; Saha, Sukumar; Mostofa, Mahbub; Awal, Md Abdul (Research in Agriculture Livestock and Fisheries, 2016)
The study compared the efficacy of some indigenous plants (Bironja, Turmeric and Veranda leaves) with that of patent drug Nilzan against Trematodiasis in sheep. Seventy five sheep suffering from trematode, aged 2-3 years and weighing about 10- 12 kg. were used for this study. The sheep were divided into 15 equal groups A, B, C, D, E, F, G, H, I, J, K, L, M, N and O. Administration of three different doses of powdered Bironja 3,6 & 9 ml /kg body wt to the group A, B, C, D and E, Turmeric at the dose rate of 2,4 & 6 ml /kg body wt to the groups F, G, H, I and J, Veranda leaves 2, 4 and 6 ml /kg body wt to the groups K, L, M, N and O showed 15-52% , 11-15% and 4-8% efficacy, respectively against trematodes in sheep. Administration of Nilzan 30 mg/kg body wt orally was highly effective 73-89% against all the species of trematodes in sheep. Among medicinal plants Bironja was found to be most effective followed by turmeric. Veranda leaves were found to be totally ineffective against trematodiasis in sheep. Res. Agric., Livest. Fish.3(1): 165-174, April 2016